2015
DOI: 10.1088/0004-637x/813/2/109
|View full text |Cite
|
Sign up to set email alerts
|

Eight Ultra-Faint Galaxy Candidates Discovered in Year Two of the Dark Energy Survey

Abstract: We report the discovery of eight new ultra-faint dwarf galaxy candidates in the second year of optical imaging data from the Dark Energy Survey (DES). Six of these candidates are detected at high confidence, while two lowerconfidence candidates are identified in regions of non-uniform survey coverage. The new stellar systems are found by three independent automated search techniques and are identified as overdensities of stars, consistent with the isochrone and luminosity function of an old and metal-poor simp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
496
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 497 publications
(518 citation statements)
references
References 113 publications
18
496
2
2
Order By: Relevance
“…The black line gives the result for the 11 classical satellites of the Milky Way, and the black dot is the estimation of Koposov et al (2008), which is based on the estimate of 45 MW satellites with MV < −5 and r < 280kpc from SDSS DR5. Recently more stellites of MW have been discovered by the Dark Energy Survey (DES; Bechtol et al 2015;Drlica-Wagner et al 2015;Koposov et al 2015), the VST-Atlas (Torrealba et al 2016) and Pan-STARRS 3π surveys (Laevens et al 2015a,b). Fig.11 of Bose et al (2017) has included these latest observed satellites, which is consistent with the data shown in our Fig.…”
Section: The Abundance Of Milky Way Satellitesmentioning
confidence: 99%
“…The black line gives the result for the 11 classical satellites of the Milky Way, and the black dot is the estimation of Koposov et al (2008), which is based on the estimate of 45 MW satellites with MV < −5 and r < 280kpc from SDSS DR5. Recently more stellites of MW have been discovered by the Dark Energy Survey (DES; Bechtol et al 2015;Drlica-Wagner et al 2015;Koposov et al 2015), the VST-Atlas (Torrealba et al 2016) and Pan-STARRS 3π surveys (Laevens et al 2015a,b). Fig.11 of Bose et al (2017) has included these latest observed satellites, which is consistent with the data shown in our Fig.…”
Section: The Abundance Of Milky Way Satellitesmentioning
confidence: 99%
“…The Dark Energy Survey (DES) recently reported the discovery of new ultra-faint dwarf galaxies (Bechtol et al 2015;Koposov et al 2015;Drlica-Wagner et al 2015;Jethwa et al 2016). We can consider their contribution to the observed luminosity function following the analysis by Jethwa et al (2016) who find that 12 of the 14 satellites have > 50% probability of having been brought in as satellites of the LMC itself (at 95% confidence).…”
Section: Satellites Of the Milky Waymentioning
confidence: 99%
“…Despite the mission's focus on cosmology, DES data have already produced a wealth of results pertaining to resolved stellar populations in the Galaxy and its vicinity, including the analysis of the structure and stellar populations in the outskirts of the Large Magellanic Cloud (LMC; Balbinot et al 2015), the identification of new Galactic companions Drlica-Wagner et al 2015;Kim & Jerjen 2015;Koposov et al 2015;Luque et al 2016), and the development of a new search for variable stars exclusively based on DES data (D. Hatt et al 2016, in preparation).…”
Section: Introductionmentioning
confidence: 99%